H-Man: design & development of forearm support with position detection ability for use in clinical settings and at home for neuro-rehabilitation - Nur' Iffah Sohaimi (2018)
The conceptual design and development of a forearm support device with position detection ability for the assisting the user’s upper extremity project is a supplementary for the H-man version two project. The H-man is a novel 2-Dimensional planar robot constituted of a mechanical design which is based on differential transmission of cables. The aim for this robotic device is to develop a cheaper alternative to current robotics stroke therapy and to provide motor control study for robotic neuro-rehabilitation. Due to its’ lightweight with simplified kinematics design, the usage of the device can be applied in homes. There is a need to include the forearm support in the H-man project as this is to assist the patients undergoing neuro-rehabilitation and thus to alleviate or to prevent pain experiencing from the user. This paper shall present the designs and consideration for the support of the upper extremity (forearm) for the rehabilitation of the stroke patients.